Profil Tingkat Kenyamanan Udara dan Hubungannya Dengan Hari Hujan di Bukit Kototabang Tahun 2010-2018 - Sulistiyono, Andi; Davi, Rendi Septa; Arifin, Ikhsan Buyung (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2020)
The change of the environment around the station of Global Atmospheric Watch Bukit Kototabang allegedly causing change in the weather factors that affect the level of discomfort. This study aims to determine the level of comfort at Bukit Kototabang GAW station and its relationship to rainy days. Study of discomfort level using calculation of Humidex was conducted using diurnal AAWS data and Fklim data resulted that does not occur